Techniques in molecular systematics and evolution (Birkhäuser, 2002)
This manual presents some of the most important techniques for data acquisition developed over the last years. The choice and justification of data analysis techniques is also an important and critical aspect of modern phylogenetic and evolutionary analysis and so a considerable part of this volume addresses this important subject. The book is mainly written for students and researchers from evolutionary biology in search for methods to acquire data, but also from molecular biology who might be looking for information on how data are analyzed in an evolutionary context